Urban wellness public facilities: on the Durban beachfront - Mkhize, Olwethu (My University, 2016)
Abstract: I have chosen to design an urban wellness public space in Durban Blue Lagoon. The aim of this research is to understand and find out the use and spatial qualities of public urban spaces that work well. The idea behind this research is to explore how this space can activate and reconnect the Durban Blue Lagoon site, by re-imagining the boundaries of the Umgeni River and how this space can connect to the city. The primary theme for my project is looking at the urban public spaces, buildings and cultural activities on the site that encourage and can attract a diversified public through an environment that enhances social and physical wellbeing. The most effective public spaces are multi-use destinations with many planned activities that create a platform of exchange and where citizens can find common ground and activity zones to relax, gather, learn and play. This theory has informed the design. The proposed site for the programme is in the city, the Durban’s Blue Lagoon recreation area, between the main road and the shoreline. The Blue Lagoon and Umgeni River junction site is close to the city and proposes opportunities for connection and engagement with the Beachwood Mangrove reserve. It is surrounded by water systems on the edges of the site, where the Indian Ocean and Umgeni River meet. Twill reflect on the Umgeni River as a conceptual starting point. The concept for the Urban Wellness Public Facility will reflect on the Umgeni River as a conceptual starting point. The site is surrounded by natural landscapes and greenery, which would further enhance the essence of enjoyment which adds to social and physical wellbeing. The programme integrates an urban wellness public facility with the principal idea of leisure, health and wellbeing spaces coming together. The programme will include an educational centre, urban wellness space, viewing platform and river taxi stop that bring awareness of social and physical wellbeing with leisure and recreational facilities. There are existing jogging, cycling, skating and fishing activities on the site and the existing jogging route will run through the urban wellness space and educational centre. The users will be the general public and tourists who will engage with exhibits, public talks and will enjoy leisure and recreational spaces.
Keywords: City planning--South Africa--Durban; Public spaces--South Africa--Durban